2015
DOI: 10.1108/par-11-2012-0056
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of IFRS in Japan: challenges and consequences

Abstract: Purpose – The purpose of this study is to provide a rigorous and holistic analysis of the main features of the Japanese accounting environment. It also raises issues related to the adoption of International Financial Reporting Standards (IFRS) in Japan. Design/methodology/approach – For the purpose of investigating the Japanese accounting system, this study applies the accounting ecology framework developed by Gernon and Wallace (1995) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 21 publications
0
30
1
Order By: Relevance
“…Tsunogaya et al, (2015) observed that a short transition period is an obstacle to IFRS adoption especially when firms are mandated to adopt and comply with IFRS. They indicated that it took a number of years for countries in the EU and Japan to fully converge to IFRS after initial adoption and that is the normal practice.…”
Section: International Journal Of Accounting and Financial Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsunogaya et al, (2015) observed that a short transition period is an obstacle to IFRS adoption especially when firms are mandated to adopt and comply with IFRS. They indicated that it took a number of years for countries in the EU and Japan to fully converge to IFRS after initial adoption and that is the normal practice.…”
Section: International Journal Of Accounting and Financial Reportingmentioning
confidence: 99%
“…The challenges of IFRS adoption vary with respect to the context of the study. Contextual issues such as political social, organizational and professional environments (Tsunogaya, Hellmann, & Scagnelli, 2015) as well as contingency firm characteristics among others may influence the kind of challenge IFRS adoption may pose to a firm.…”
Section: Introductionmentioning
confidence: 99%
“…Tsunogaya et al (2011) put this resistance in perspective by means of an extensive historically oriented analysis of accounting models prevailing in Japanese accounting thought and embedded in the regulatory system. Tsunogaya (2016) and Tsunogaya et al (2015) provide some insight into the structure of the debate over IFRS by analyzing the record of deliberations of the BAC during 2011 and selected episodes in 2008-2013, respectively. As for France and Germany (see prior sub-sections), the debate about the suitability of IFRS for national circumstances is partly made available to an international audience.…”
Section: Japanmentioning
confidence: 99%
“…26. Tsunogaya (2016) and Tsunogaya et al (2015) have made a start along these lines by analyzing minutes of the BADC (or BAC, as it was known by then) for the period 2008-2013. 27.…”
Section: Fundingmentioning
confidence: 99%
“…The research states that both China and USA first aims to determine the benefits of IFRS before fully converging to it. Tsunogaya et al (2015) investigates the Japanese accounting system and the adoption of IFRS in Japan. The research also deals with the problems faced by the companies whose securities trade in a public market.…”
Section: Literature Reviewmentioning
confidence: 99%